The impact of liver steatosis on the severity of COVID-19 in patients with chronic coronary syndrome - M.M. Zhaivoronok; S.Ye. Mostovyi; O.M. Safonova (Gastroenterologìa)
Background. The coronavirus disease 2019 (COVID-19) remains one of the most pressing global health issues today. According to contemporary literature, COVID-19 may trigger a deterioration of liver function in patients with or without pre-existing liver diseases. It is known that COVID-19 can lead to the reactivation of pre-existing liver conditions, such as metabolic dysfunction-associated steatotic liver disease (MASLD), causing its further progression to liver cirrhosis. Patients with chronic coronary syndrome (CCS) are most vulnerable to coronavirus disease and its complications (including MASLD). Therefore, prognostic ultrasound assessment of liver steatosis in terms of COVID-19 severity and complications is crucial. The aim of our study was to evaluate the impact of MASLD on the severity of COVID-19 in patients with chronic coronary syndrome. Materials and methods. In this study, we evaluated multidetector computed tomography (MDCT) scans of the liver from 120 patients (41 women, average age 63.73 years) who were referred for lung examination and had confirmed COVID-19 and CCS. We measured the attenuation values of the MDCT signal for the liver and spleen and calculated the liver-to-spleen ratio (LSR) to detect MASLD. Univariate and multivariate logistic regression analyses were used to identify independent early predictors of severe COVID-19 in patients with CCS. Results. Liver density and LSR in MASLD were significantly lower in patients who stayed in the intensive care unit. The prevalence of severe disease was higher in patients with CCS combined with MASLD than in the group without MASLD (odds ratio (OR) 3.512, 95% confidence interval (CI) 1.685–6.140, P < 0.05). After adjusting for age and comorbidities, including diabetes, chronic obstructive pulmonary disease, and chronic kidney disease, multivariate logistic regression analysis indicated that MASLD is an independent risk factor for the severity of COVID-19 (OR 3.675, 95% CI 1.495–7.263, P = 0.020) in patients with CCS. Conclusions. MDCT of the liver during chest organ imaging plays a crucial role in the diagnosis of COVID-19 and can provide information regarding the disease prognosis. MASLD is an important marker of poor prognosis in patients with CCS and can be detected on MDCT through LSR assessment.